2022
DOI: 10.3389/fphar.2022.833303
|View full text |Cite
|
Sign up to set email alerts
|

Dose Optimisation of Posaconazole and Therapeutic Drug Monitoring in Pediatric Patients

Abstract: Experience in the clinical use of posaconazole (PCZ) in pediatric patients is limited, and no specific dose recommendations exist. This study aimed to investigate an appropriate dosing regimen, and assess the exposure-response relationships of PCZ in children. We reviewed the medical records of inpatients aged <18 years who subjected to PCZ concentrations monitoring. Clinical data, PCZ dosing and monitoring data were collected. A total of 375 PCZ trough concentrations (Cmin) from 105 pediatric patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In healthy adults, PPIs have been shown to reduce maximal serum concentration of PSZ after OS dosing by around 46% [ 20 ]. In children, one population PK analysis estimated a 42% reduction in OS bioavailability during concomitant PPI administration (and no or limited effect of H2RAs), while another study reported a significant decline in target attainment percentage while receiving both OS and PPIs [ 13 , 34 ], which are similar if not somewhat reduced effects compared with our study results. These findings of heavily reduced suspension bioavailability of PSZ are underpinned by its poor solubility, solubility rate-limited absorption (i.e., Biopharmaceutical Classification System [BCS] class II), and, most importantly, its pH-dependent solubility (i.e., reduced solubility at elevated gastric pH) that have been extensively characterized in the literature [ 35 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In healthy adults, PPIs have been shown to reduce maximal serum concentration of PSZ after OS dosing by around 46% [ 20 ]. In children, one population PK analysis estimated a 42% reduction in OS bioavailability during concomitant PPI administration (and no or limited effect of H2RAs), while another study reported a significant decline in target attainment percentage while receiving both OS and PPIs [ 13 , 34 ], which are similar if not somewhat reduced effects compared with our study results. These findings of heavily reduced suspension bioavailability of PSZ are underpinned by its poor solubility, solubility rate-limited absorption (i.e., Biopharmaceutical Classification System [BCS] class II), and, most importantly, its pH-dependent solubility (i.e., reduced solubility at elevated gastric pH) that have been extensively characterized in the literature [ 35 ].…”
Section: Discussionsupporting
confidence: 75%
“…Bioavailability has been observed to be dose-limited in both adults (up to 800 mg/dose) [ 41 ] and children (up to 700 mg/dose) [ 13 , 14 ], although a full exploration of nonlinearity, as well as additional dose-limiting factors such as palatability, has not been conducted. The target serum concentrations for TDM have been suggested by the British Society of Medical Mycology and supported by a previous retrospective analysis study in Chinese children [ 34 ]. These are general guidelines for maximizing prophylaxis and treatment efficacy, and thus the target attainment analysis does not guarantee favorable outcomes (prevention of breakthrough infections or complete cure of IFD) in all cases, especially in instances of drug-resistant pathogens.…”
Section: Discussionmentioning
confidence: 82%